Empowering students as questioners: skills, strategies, and structures to realize the potential of every learner - Walsh, Jackie A. (Thousand Oaks, California: Corwin, 2021)
"The first edition of Thinking Though Quality Questioning provided teachers with an accessible, research-based blueprint for developing student meta-cognitive skills and ensuring that students take responsibility for their own learning. Walsh and Sattes use the findings of cognitive scientists to highlight quality questioning behaviors and explain how to connect these to discrete student meta-cognitive outcomes. Each chapter includes teacher best practice in questioning and relates this to how students think and how they can be trained to manage their own learning. This second edition hones in on the concept of Student Response-Ability, defined as: "the student's capacity to form a thoughtful response when presented with a question or issue, the confidence to express this thinking verbally and/or through action, and the commitment to contribute to a learning community." The new edition restructures the book around student "I" statements or mindsets that enforce its theme of student-centricity. It also expands on the concept of feedback by showing teachers how to help students both receive it and give it. It provides new information on making the classroom safe and healthy for students. About half of the content will be new or restructured"--
Includes bibliographical references and index.
Keywords: Inquiry-based learning; Questioning; Teacher-student relationships